Effect of Capital Adequacy Ratio and Operational Efficiency Ratio on Return on Assets at PT Bank Negara Indonesia Tbk. - Amanda Adelina Putri; Dadang Hermawan; Endang Hatma Juniwati; Tjetjep Djuwarsa (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study examines the effect of Capital Adequacy Ratio (CAR) and Operational Efficiency Ratio (OER) on PT Bank Negara Indonesia (Persero) Tbk's Return on Assets (ROA). 2010-2020 This analysis utilizes data from PT. Bank Negara Indonesia (Persero) Tbk's 2010-2020 Financial Report. This study uses secondary data from financial statements and then uses multiple linear regression as a quantitative descriptive method IBM SPSS version 20 was used in this investigation. The regression model in this study successfully completed a test of classical assumptions, indicating that the data are normally distributed and devoid of multicollinearity, heteroscedasticity, and autocorrelation. CAR and OER were both found to have negative impacts on ROA by multiple regression analysis. Hence, Between 2010 and 2020, the ROA of PT Bank Negara Indonesia (Persero) Tbk will be impacted by CAR and OER.